Chitogel with deferiprone following endoscopic sinus surgery: improved wound healing and microbiome - Megow, Anna; Bouras, George; Alsuliman, Yazeed; Cooksley, Clare; Vyskocil, Erich; Murphy, William; Vreugde, Sarah; Wormald, Peter-John (Frontiers in Surgery, 2024)
Adhesion formation, sinus ostial narrowing and presence of pathogenic bacteria are associated with poor outcomes following endoscopic sinus surgery (ESS) for chronic rhinosinusitis (CRS). Chitogel has been shown to improve wound healing, restore a healthier microbiome and reduce post-operative infections post ESS. Deferiprone has antibacterial properties and has been shown to reduce adhesion formation. The aim of the study was to assess whether the addition of low concentration deferiprone to Chitogel further improves surgical outcomes following ESS compared to Chitogel alone.In this double-blinded trial, 45 patients undergoing ESS were prospectively recruited. At the end of surgery, patients were randomised to receive Chitogel alone, Chitogel with 1 mM of deferiprone or Chitogel with 5 mM of deferiprone to one side of the sinuses (allowing the other side to serve as control). Patients underwent routine follow-up with symptom questionnaires and nasoendoscopies performed at 2-, 6-and 12-weeks post-operative. Sinus ostial measurements, microbiology and microbiome swabs from bilateral middle meati were collected intraoperatively and at 12 weeks post-operative.A significant improvement in the endoscopic appearance of the sinuses and frontal ostial patency was noted at 12 weeks postoperative (p<0.05) in all three treatment groups compared to control. There was no significant difference noted between patients who received Chitogel alone, compared to Chitogel with 1 mM or 5 mM deferiprone.Chitogel alone, Chitogel with 1 mM deferiprone and Chitogel with 5 mM deferiprone used following ESS led to a significant improvement in endoscopic appearance of the sinuses and frontal ostial preservation at 12 weeks postoperative. No significant difference was found with the addition of deferiprone to Chitogel.